2023
DOI: 10.3390/curroncol30010074
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the Prevention of Oral Mucositis in Patients Receiving Cancer Treatment: Evidence from Randomised Controlled Trials

Abstract: Oral mucositis is a common and most debilitating complication associated with cancer therapy. Despite the significant clinical and economic impact of this condition, there is little to offer to patients with oral mucositis, and the medications used in its management are generally only palliative. Given that mucositis is ultimately a predictable and, therefore, potentially preventable condition, in this study we appraised the scientific literature to evaluate effective methods of prevention that have been teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 112 publications
0
23
0
Order By: Relevance
“…Currently, physiological saline mouthwash is the commonly used treatment method for oral mucositis in clinical practice [16] . It can reduce the residual amount of food in the oral cavity, avoid the reproduction of bacteria in the oral cavity, and also keep the oral cavity in a normal physiological environment, relieve the dryness of the mouth caused by reduced saliva secretion [6,7,16] . However, it has no antibacterial effect and the therapeutic effect on oral ulcers is not good [11,16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, physiological saline mouthwash is the commonly used treatment method for oral mucositis in clinical practice [16] . It can reduce the residual amount of food in the oral cavity, avoid the reproduction of bacteria in the oral cavity, and also keep the oral cavity in a normal physiological environment, relieve the dryness of the mouth caused by reduced saliva secretion [6,7,16] . However, it has no antibacterial effect and the therapeutic effect on oral ulcers is not good [11,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucositis can cause unbearable pain, broad ulceration, double the risk of infection, prolonged hospitalization, increased hospitalization costs, and other adverse factors [5,6] . Relevant studies have indicated that prophylactic medication and appropriate oral care can prevent or alleviate the occurrence of oral mucositis in patients, accelerate its healing, and improve patients' quality of life [5][6][7] . During the period of cytotoxic chemotherapy or head and neck radiotherapy, continuous mouth rinsing with ice cubes or ice chips or drinking ice-containing beverages can cause vasoconstriction of the oral mucosal blood vessels, reduce the oral distribution of cytotoxic drugs, and effectively reduce the incidence of oral mucositis [7,8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment for OM remains centered on oral care, mouthwashes, and the use of steroid ointments, and no new treatments have been found. Colella et al state that OM is a common and most debilitating complication associated with the treatment of malignancy and that despite the signi cant clinical and economic consequences of this condition, there is little to offer patients with OM and the medications used in its management are generally only palliative [3]. RV Lalla.…”
Section: Introductionmentioning
confidence: 99%
“…2 Graduate School of Advanced Science and Engineering, Hiroshima University, Hiroshima, JAPAN. 3 Department of Oral Surgery, Hiroshima Red Cross & Atomicbomb Survivors Hospital, Hiroshima, JAPAN…”
mentioning
confidence: 99%